Reliability analysis of Bangladesh power system - Yasmin, Farzana; Samad, Sazeed Mohammad Ibne; Haque, Md. Safat Samir (BRAC University, 2013)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2012.